Maquet III procedure: what remains after initial complications--long-term results - Fonseca, Fernando (2013)
Background: Maquet III procedure, unloved due to its complications (2% to 59%), has been progressively abandoned. At long-term follow-up, what happens to patients with complications that exceeded the initial ones (Acta Orthop Scand 60:20, 1989)? We retrospectively studied patients who were submitted to Maquet III procedure, by functional and radiologic long-term outcomes, in order to determine if this surgery has or has not fulfilled its initially proposed objectives. From 1970 to 1991, 116 patients benefit from the Maquet III procedure. From this, we were able to review in 2011, 23 patients (25 knees) who went through a single Maquet III procedure. Of these patients, 52% were males. Age at surgery was 39.7 ± 11.4, with a postoperative follow-up of 27.2 ± 3.1 years. Methods: A questionnaire has been prepared for collecting data, and it has been supplemented by clinical records. We evaluated the preoperative complaints, postoperative complications, and range of motion during the recovery time, as well as the postoperative pain-absence period. All patients underwent an objective assessment using the visual analog scale (VAS) at rest and activity, and the Kujala patellofemoral scoring system. A radiological assessment was also made in order to evaluate the arthrosis degree. The bicondylo-patellar angle described by Delgado-Martins (Arch Orthop Traumat Surg 96:303–304, 1980) was used to measure patellar tilt, and the Caton-Deschamps index to calculate the patellar height. Results: Only one knee had benefited from a total knee arthroplasty (20 years after the Maquet III procedure). Preoperative complains were mainly anterior knee pain, crepitus, and patellar instability. Nowadays, 10 patients (40%) still are pain free. Others had an average period without pain of 19.1 ± 6.1 years. VAS at rest was 1.7 ± 0.7 and in activity 4.4 ± 3.0. KPS was 61.9 ± 22.3 points. X-ray shows that 40% had a Kellgren-Lawrence grade of 1 at the patellofemoral joint. Conclusion: Maquet proposed this technique for knee-pain relief, maintenance of the knee range of motion, and for slowly progressive osteoarthritic development. Viewed in a dispassionately way, we could notice that the initial objectives of this procedure were completely achieved. A part of 80% of the initial population was lost during follow-up, which may compromise the conclusions, perhaps, it is time to reflect again on this solution, so unloved by so many.